Surface Roughness and Color Stability of Single-Shade Composite vs. Multi-Shade Composite: An In vitro Study - Alex, Angela; Venkatesh, Vijay (Medical Science: Trends and Innovations Vol. 11, 2025)
Composite resin materials are a popular choice for direct tooth-colored restorative purposes due to their excellent aesthetic qualities and versatility. The key determinants that impact the visual aspect of the restoration are gloss, surface roughness, and color stability. Research indicates that there is a direct correlation between the level of roughness on a composite resin surface and the likelihood of discoloration. To meet the increasing patients' esthetic demands, achieving an ideal color match between natural tooth tissues and restorative material is crucial. However, clinicians face challenges in replicating the color of natural dentition in response to the heightened aesthetic demands. The aim of this study was to compare and evaluate the surface roughness and color stability of a single-shade and multi-shade composite resin after subjecting it to toothbrush simulation and immersion in coffee and an aerated drink. Ten single-shade composite resins and 10 multishade composite resins were packed into a Teflon mold and light cured. Preoperative surface roughness values were evaluated using a surface profilometer. Toothbrush abrasion was simulated using a toothbrushing simulator. All these resin molds were then evaluated for initial color using a spectrophotometer machine (Konica Minolta, Japan). Five resin molds were then immersed in a beaker containing coffee for seven days and five resin molds were immersed into a beaker containing an aerated drink for seven days. Following this, the resin molds were reevaluated for color stability using a spectrophotometer machine. Data regarding surface roughness and color stability in multi-shade and single shade composites was investigated for normality using the Shapiro-Wilk test and showed a normal distribution. Descriptive statistics were derived as mean and standard deviation. The results of this study show that single-shade composite showed increased discoloration when compared with multishade composite resin. Also, there is a statistical difference between the single-shade composite and multishade composite when it comes to surface roughness and discoloration. The multishade composite (spectrum), which was used in this study, has bisphenol Aglycidyl methacrylate as its primary monomer compared to the singleshade composite (Omnichroma), which had triethylene glycol dimethacrylate as the primary monomer. Based on this investigation, it has been suggested that conducting clinical trials on the color alteration of singleshade resin composites would be advantageous. With the limitations of the present study, it can be concluded that single-shade composite resins have more discoloration potential in beverages than multi-shade composite resins.